Immigration and Wage Dynamics: Evidence from the Mexican Peso Crisis - Joan Monras (Institute for the Study of Labor (IZA), 2015)
How does the US labor market absorb low-skilled immigration? I address this question using the 1995 Mexican Peso Crisis, an exogenous push factor that raised Mexican migration to the US. In the short run, high-immigration states see their low-skilled labor force increase and native low-skilled wages decrease, with an implied local labor demand elasticity of -.7. Internal relocation dissipates this shock spatially. In the long run, the only lasting consequences are for low-skilled natives who entered the labor force in high-immigration years. A simple quantitative many-region model allows me to obtain the counterfactual local wage evolution absent the immigration shock.
Keywords: F22; J20; J30; 330; international and internal migration; local shocks; local labor demand elasticity